End-to-side nerve transfer in neuropathic pain post brachial plexus injury - Nur Dina A.; Shalimar A. (Faculty of Medicine, University of Malaya, 2024)
We report a case of a 59-year-old gentleman with complete left brachial plexus injury. He presented with chronic pain over the dorsum of his left hand since the injury eight years ago. Medical treatment had been optimised but the pain still persist. End-to-side nerve transfer was done involving superficial sensory radial nerve and median nerve to alleviate the pain. The surgery was considered successful as the patient claimed that the pain score had reduced a few weeks postoperatively. However, there was no sensory recovery and functionally no improvement was observed. 2018, Faculty of Medicine, University of Malaya. All rights reserved.